Faktor-Faktor yang Berhubungan dengan Kejadian Pre Hipertensi pada Mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan (FKIK) Universitas Jambi - Nadya Pramesti; Marta Butar Butar; Adelina Fitri; Rd. Halim (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Prehypertension is a condition in which blood pressure is elevated but has not yet reached the threshold for hypertension, with systolic pressure of 120–139 mmHg and diastolic pressure of 80–89 mmHg. Based on data from the Jambi Provincial Health Office in 2024, hypertension ranked second among the top 10 diseases, accounting for 23.21% of cases in individuals aged over 15 years. A preliminary survey conducted among 20 students of the Faculty of Medicine and Health Sciences, Universitas Jambi, found that 8 students (40.0%) had prehypertension and 1 student (5.0%) had hypertension. This study employed a quantitative approach with an analytic observational method using a cross-sectional design. The population consisted of students from various study programs at the Faculty of Medicine and Health Sciences, Universitas Jambi, from the 2023, 2024, and 2025 cohorts. A total of 176 respondents were selected using stratified random sampling. Data were analyzed using the Chi-square test with a significance level of α = 0.05. The results of the study showed that there was a relationship between nutritional status (p=0.0001), sodium intake (p=0.0001), stress conditions (p=0.046), sleep apnea (p=0.0001), and gender (p=0.023) with the incidence of prehypertension. There are significant associations between nutritional status, sodium intake, stress condition, sleep apnea, and sex with the incidence of prehypertension.